Implementation of Signature Validity On Electronic Documents in Proof Indonesian Civil Procedure Law - Khusniyah, Nurul Khotimatul; Widayati, Widayati (Universitas Islam Sultan Agung, 2021)
This study aims to identify and analyze the acknowledgment of signatures on an electronic document in the evidence of civil procedural law in Indonesia, and to find out and analyze the implementation of civil dispute resolution submitted by the parties by means of electronic documents signed with digital signatures. The method used in this research is to use an empirical juridical approach. Electronic documents, in this case digital signatures, can be used as evidence in court, which is an extension of the evidentiary law in Indonesia after the ITE Law, but only has the power of proof as an underhand deed not as an authentic deed. In the process of settling a lawsuit for civil proceedings through litigation media, it is carried out amicably first by means of a peace made by the party concerned without the assistance of an authorized official. Efforts to settle through non-litigation media can be carried out in three ways, including arbitration, negotiation, and mediation.